2019
DOI: 10.21873/anticanres.13326
|View full text |Cite
|
Sign up to set email alerts
|

Association of Notch and Hedgehog Pathway Activation With Prognosis in Early-stage Colorectal Cancer

Abstract: Background/Aim: Early-stage colorectal cancer (CRC) carries a wide range of survival probabilities. Novel biomarkers in this setting are eagerly awaited. Cancer stem cells (CSCs) are considered one of the reasons for treatment failure. This study sought to determine whether activation of pathways governing the function of CSC's could correlate with treatment outcomes. Materials and Methods: Tumor specimens from 325 patients were analyzed with immunohistochemistry (IHC) for Hedgehog and Notch pathway activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Bernasconi-Elias and colleagues generated Notch3 inhibitory antibodies that exhibited strong antileukemic activity in cell lines as well as tumor xenografts with Notch3 activating mutations [33]. free survival (DFS) and overall survival (OS) [35]. Another study also confirmed a link between high levels of Notch3 and aggressive malignant colorectal cancer cell phenotype [36] and tumor recurrence after surgical resection of CRC [37,38].…”
Section: Discussionmentioning
confidence: 93%
“…Bernasconi-Elias and colleagues generated Notch3 inhibitory antibodies that exhibited strong antileukemic activity in cell lines as well as tumor xenografts with Notch3 activating mutations [33]. free survival (DFS) and overall survival (OS) [35]. Another study also confirmed a link between high levels of Notch3 and aggressive malignant colorectal cancer cell phenotype [36] and tumor recurrence after surgical resection of CRC [37,38].…”
Section: Discussionmentioning
confidence: 93%
“… 153 The positive expression of Notch3 protein is an unfavorable prognostic factor of disease-free survival (DFS) and overall survival (OS). 154 However, the functions of notch2 and notch4 are opposite to them, their overexpression can block the proliferation, invasion or migration of cancer cells. 155 , 156 Meanwhile, multiple Notch signaling pathway related mechanisms play a significant role in metastatic CRC(Fig.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…In the intestinal epithelium, Notch signaling plays a crucial role by regulating cell differentiation, determining the lineage fate of TA cells. Activation of the Notch pathway relies on the interaction of five ligands (Jagged1/2 and Delta like-1/3/4) and four receptors (Notch1/2/3/4) (Rallis et al., 2019).…”
Section: Regulation Of Intestinal Homeostasismentioning
confidence: 99%